Analysis of correlaton land subsidence in south semarang with geological conditions using overlay method - Maiyudi, Riko (Universitas Negeri Padang, 2020)
Land subsidence in the city of Semarang based on the results of GPS measurements is quite significant. Land subsidence is a phenomenon that can result in losses and have a negative impact on the environment, therefore research is needed to examine the characteristics of land subsidence. One of the factors causing land subsidence is the influence of the geological conditions of the area, Semarang is a coastal city that contains alluvial deposits. Especially in northern Semarang. The phenomenon of land subsidence occurred in this region. Naturally, the area experienced a decrease in land surface due to the material nature of alluvial deposits. Therefore, the relationship of subsidence to geological conditions can be identified by the overlay method. The results of this study found a correlation between geological conditions and subsidence in North Semarang.